2017
DOI: 10.1039/c7cp02382k
|View full text |Cite
|
Sign up to set email alerts
|

Growth of two dimensional silica and aluminosilicate bilayers on Pd(111): from incommensurate to commensurate crystalline

Abstract: Two-dimensional (2D) silica (SiO) and aluminosilicate (AlSiO) bilayers grown on Pd(111) were fabricated and systematically studied using ultrahigh vacuum surface analysis in combination with theoretical methods, including Auger electron spectroscopy, X-ray photoelectron spectroscopy, low-energy electron diffraction (LEED), scanning tunneling microscopy (STM), and density functional theory. Based on LEED results, both SiO and AlSiO bilayers start ordering above 850 K in 2 × 10 Torr oxygen. Both bilayers show he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 51 publications
3
47
1
Order By: Relevance
“…This conclusion is further supported by STM studies performed in another UHV chamber. At sub-monolayer coverages, silica forms irregularly-shaped islands which coalesce at increasing coverage ( Although our results generally agree with those reported by Jhang et al [16] also showing the formation of a bilayer film on Pd(111), none of our films exhibited long-range ordering. We have to recall, however, that on Ru(0001) the bilayer silica films may also form crystalline and amorphous phases (often coexisting) depending on the preparation.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This conclusion is further supported by STM studies performed in another UHV chamber. At sub-monolayer coverages, silica forms irregularly-shaped islands which coalesce at increasing coverage ( Although our results generally agree with those reported by Jhang et al [16] also showing the formation of a bilayer film on Pd(111), none of our films exhibited long-range ordering. We have to recall, however, that on Ru(0001) the bilayer silica films may also form crystalline and amorphous phases (often coexisting) depending on the preparation.…”
Section: Resultssupporting
confidence: 92%
“…[5] Such comparison would provide a deeper understanding of the role of a metal substrate on the atomic structure of a silica film and its reaction at the interface. In the course of our studies we have learned that Altman and co-workers studied the growth of silica on Pd(111) for comparison with Pd(100) [16]. The authors found that the silica bilayer starts ordering above 850 K and forms an incommensurate crystalline structure resulted in a Moire pattern.…”
Section: Introductionmentioning
confidence: 96%
“…On high oxygen affinity metal substrates, such as Mo, silica forms only chemically bonded monolayer films [52]; on inert metals, such as Pd and Pt, the film-substrate interaction is weaker and forms amorphous decoupled (or crystalline and nonconmensurate) bilayer films [43,[53][54][55]; and on intermediate metal supports, such as Ru, exhibits both types of behaviors [56][57][58]. Jhang et al has shown by doping the silica films that the structure of the film is also heavily affected by the strain and charge transfer with the metal substrate [53]. Interestingly, silica bilayer films interact only through van der Waals forces with the metal substrate, as was determined by infrared reflection absorption spectroscopy and DFT calculations [58].…”
mentioning
confidence: 99%
“…2D silica and silicate films can be prepared on metal substrates, including Pd(100) and Pd(111), and Ru(0001) and metal alloys . While it is good approach to study 2D materials by combination of experimental and theoretical techniques, it is not a practical method for the preparation of 2D zeolites.…”
Section: D Zeolitesmentioning
confidence: 99%
“…Doping with Al can cause the softening of the material, reducing lattice strain energy and formation of a commensurate phase due to the stronger interaction between the metal and the aluminosilicate layer. Stronger interaction in the latter case corresponds to the electrostatic interaction and partial charge transfer between negatively charged aluminosilicate layer and the metal substrate and results in PdO bond formation . Systems prepared by deposition of silica on metal substrates do not have any silanol groups on their surface and they can be considered as perfect models for investigation of various properties using numerous surface science experimental characterizations.…”
Section: D Zeolitesmentioning
confidence: 99%